2021
DOI: 10.1111/php.13414
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Doxycycline and InGaAlP Diode Laser at 660 nm Wavelength in the Treatment of Periodontitis Induced in Rats: In Vivo Study

Abstract: This study evaluated the influence of Doxycycline (DOX) and Low-Intensity Laser (LIL) (InGaAlP diode laser) as scaling and root planing (SRP) adjuvants in the treatment of periodontitis induced in rats. The rats received periodontal disease induction, and after 7 days, the ligature was removed, and the animals were divided into groups/treatments: NTreceive no treatment; SRP-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Astuti et al used doxycycline-assisted photodynamic therapy in the gingival sulcus of mice with periodontitis and successfully eliminated Porphyromonas gingivalis bacteria, resulting in effective improvement (16). A similar improvement by using laser radiation and doxycycline administered in gingival sulcus of rats with induced periodontitis was achieved in a study conducted by Silveira et al (50). Also, numerous studies found that tetracycline underwent oxidation and produced reddish-colored products when exposed to light (17).…”
Section: Resultsmentioning
confidence: 59%
“…Astuti et al used doxycycline-assisted photodynamic therapy in the gingival sulcus of mice with periodontitis and successfully eliminated Porphyromonas gingivalis bacteria, resulting in effective improvement (16). A similar improvement by using laser radiation and doxycycline administered in gingival sulcus of rats with induced periodontitis was achieved in a study conducted by Silveira et al (50). Also, numerous studies found that tetracycline underwent oxidation and produced reddish-colored products when exposed to light (17).…”
Section: Resultsmentioning
confidence: 59%
“…Doxycycline (Dox) is a synthetic bacteriostatic tetracycline effective in periodontitis 11 , 12 . As a broad-spectrum antibiotic, Dox can affect the activity of periodontal pathogens.…”
Section: Introductionmentioning
confidence: 99%